Marine Spatial Planning Through Management Linkage Approach - Salem, Albotoush Reda Abdel Aziz (2022)
Coastal areas have always been a ‘hub’ of resources and a target for infrastructure development, yet, considered vulnerable in many parts of the world. And these are often face dilemmas associated with urbanization, adverse climatic, and environmental change for living organisms, along with the absence of the implementation of an integrated approach in managing these issues. Therefore, new management approaches had been tried such as Integrated Coastal Zone Management (ICZM) and Marine Spatial Planning (MSP) to managing coasts in a sustainable and most effective manner while accommodating its dynamism. However, some challenges appeared related to the management approaches' such as the interference between ICZM (up to 3-12 nm) and MSP (up to 200 nm) from the coastline, not adhering to approved plans (Penang’s ICZM as a case study), the random approach of choosing the management authorities in case of MSP. Thus, the main aim of this thesis is to develop innovative approaches capable of enhancing the conceptualization of MSP and it’s implementation by addressing the following objectives; 1- to assess the current state-of-the-art (from around the globe; particularly the European experience) forms of MSP governance and the organizations in charge of implementation, 2- to determine the organization most suited as an MSP authority, 3-To propose a methodology to link/integrate MSP and ICZM, and 4- to evaluate the efforts associated with ICZM in the state of Penang.